The Relationship between Head Nurse Controlling Function and the Completeness of Nursing Care Documentation - Thessalonicha Prayssi Kosakoij; Hariany Theresia Sipangkar (GLOBAL HEALTH SCIENCE GROUP, 2026)
Nursing care documentation (ASKEP) is a vital clinical quality indicator influenced by ward unit management. This study analyzed the relationship between the head nurse's management controlling function and the completeness of ASKEP at RSUD Yowari, Papua. A quantitative analytical design with a cross-sectional approach was conducted among 34 staff nurses. Data were collected via standardized questionnaires and observation checklists, then analyzed using Fisher's Exact Test (). Respondents were predominantly female (94.1%), early adults (91.2%), held a Diploma-III (85.3%), and had <10 years of tenure (58.8%). Head nurse controlling was perceived as poor (76.5%), yet ASKEP completeness was high/complete (82.4%). Bivariate analysis indicated no significant relationship between variables (p=1.000; ). Staff documentation compliance is systemically independent, driven by external macro-organizational pressures (systemic-driven compliance) including national accreditation preparation and professional-legal safety motivation, rather than internal daily unit supervision.